Pengaruh Problem Solving Berbasis STEM terhadap Keterampilan Psikomotorik Siswa Sekolah Dasar - Chania Roshanza Ikhsani; Ramdhan Witarsa (Universitas Negeri Makassar, 2023)
The ability problem solving is one of the abilities that primary school students must have when participating in science, technology, engineering, and mathematics-based learning in the classroom. Problem solving learning based on science, technology, engineering, and mathematics is important for students' psychomotor skills. This research aims to measure how much influence problem solving based on science, technology, engineering and mathematics has on the psychomotor skills of primary school students. The method used in this research is quasi-experimental.The data collection technique used was the observation of students' psychomotor skills. The results of this study can show that problem solving based on science, technology, engineering, and mathematics does not have a significant effect on the psychomotor skills of fourth grade primary school students. Therefore, this research cannot be used as a reference in measuring the psychomotor level of primary school students.